2021
DOI: 10.54821/uiecd.1033651
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Tourism-induced EKC Hypothesis: The Case of Turkey

Abstract: This paper examines the existence of relationship between international tourist arrivals (TA), and Carbon dioxide emissions per capita (CO2) in Turkey over the period . We also use energy use per capita (EU) and GDP per capita (GDP) as a control variables. The autoregressive distributed lag (ARDL) bounds test approach was applied to analyze the long-run relationship among the variables. The results confirmed the validity of the tourism-induced Environmental Kuznets Curve (EKC) hypothesis. An increased tourism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…All of this has strengthened the importance of sustainability in tourism more than in other sectors, and Turkey is concerned with developing sustainable tourism [ 77 ]. Turkey focuses on climate change [ 81 ] and is interested in environmental protection and the use of renewable energy [ 43 ]. In the Black Sea region, Turkey intends to focus on the development of rural tourism [ 82 ] and ecotourism, and also on strategic initiatives for sustainable tourism, that is, planning, managing and monitoring the tourism sector through long-term sustainable approaches [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of this has strengthened the importance of sustainability in tourism more than in other sectors, and Turkey is concerned with developing sustainable tourism [ 77 ]. Turkey focuses on climate change [ 81 ] and is interested in environmental protection and the use of renewable energy [ 43 ]. In the Black Sea region, Turkey intends to focus on the development of rural tourism [ 82 ] and ecotourism, and also on strategic initiatives for sustainable tourism, that is, planning, managing and monitoring the tourism sector through long-term sustainable approaches [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…This only happens in regions with an educated population because the educational advantage increases the opportunity to attract tourists [ 42 ]. Kilavuz et al (2021) [ 43 ] examined the relationship between international tourist arrivals and carbon dioxide emissions per capita in Turkey over the period 1960–2015. As tourism demand increases, so does pollution, until the tourism sector reaches a certain level of development and the amount of greenhouse emissions begins to decrease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result showed that international visitors have a positive impact on CO2 emissions. Kılavuz et al (2021Kılavuz et al ( ) 1960Kılavuz et al ( -2015 Turkey ARDL Test…”
Section: Panel Data Analysismentioning
confidence: 99%
“…Studies on the relationship between tourism and CO2 emissions in the literature generally explain the issue through various variables such as tourism, energy, economic growth, environment (Lee and Brahmasrene, 2013;Katircioglu et al, 2014;Dogan et al, 2017;Liu et al, 2019;Zhang, 2021 Rahman et al, 2022;Katircioglu and Katircioglu, 2022;Duran and Bozkaya, 2022), as well as renewable energy and foreign trade (Jebli, 2019;Salahodjaev, 2022). Meanwhile, some studies examine the relevant topic, considering the potential connections between socio-economic factors such as tourism and the environment, in a notably Environmental Kuznets Curve (EKC) framework (Katircioğlu, 2014;De Vita et al, 2015;Zaman et al, 2016;Kılavuz et al, 2021). In specific studies related to the topic in the literature, emphasis is placed on tourism revenue and visitor numbers (Al-Mulali et al, 2015;Sharif et al, 2017;Eyuboglu and Uzar, 2019;Koçak et al, 2020;Le and Nguyen, 2020).…”
Section: Panel Data Analysismentioning
confidence: 99%